PELAKSANAAN PEMILIHAN UMUM TAHUN 2024 DITINJAU DARI ASPEK SOSILOGI HUKUM - Putra Said Aiditya (JOURNAL IURIS SCIENTIA, 2024)
Presidential Elections (Pilpres) and General Elections (Pemilu) are the main pillars of the Indonesian democratic system which illustrate the power of the people's vote. Central Java province, with its significant population and cru- cial role in national politics, plays an important role in determining the coun- try's future. In the aspect of legal sociology, the presidential election and gen- eral elections have a significant social, cultural and legal impact on society. Central Java Province, which is geographically, ethnically, religiously, cul- turally and socially diverse, provides its own dynamics in the political pro- cess. In 2024, presidential elections and general elections will be held again in Indonesia, including in Central Java Province. Therefore, this research aims to understand and analyze the social, cultural and legal impacts of the 2024 presidential and general elections in the Central Java Province region. By examining the role of social and cultural factors, as well as the role of legal institutions in overcoming election challenges and election conflicts, this research aims to maintain election integrity, increase community participa- tion, and maintain social and political stability during and after the 2024 Presidential Election and General Election in Central Java Province.